Development of Visual Portion Sizes to Increase Housewives' Knowledge of Food Portions in an Effort to Reduce Food Waste - Swamilaksita, Prita Dhyani; Baliwati, Yayuk Farida; Sa’pang, Mertien; Harna, Harna; Laili, Nur Ahzaini; Putri, Rizkansa Insyira (East Asian Journal of Multidisciplinary Research, 2024)
Food Waste (FW) is one of the most pressing social, economic, and environmental issues affecting environmental sustainability, by reducing FW, goal 12 of the SDGs, related to responsible food consumption and production can be achieved. The economic loss due to FW is equivalent to a loss of IDR 213-551 trillion per year. Based on wasted energy and protein, 61-125 million Indonesians could be fed if there was no food waste. Studies show that the amount of food wasted is equivalent to feeding 125 million people to alleviate poverty and address stunting in Indonesia. Most food waste is generated at the consumption stage. Eating food wisely and according to portions can help reduce food waste.  Through Visual Portion Sizes (VPS), it is hoped that housewives' knowledge about food portions can increase, so that food waste can be minimized or zero waste can be achieved. Respondents in this study amounted to 30 people who are food managers in households. The results stated that there was a significant difference between the knowledge of household food managers before and after education (p<0.05). Respondents already understood the principles of balanced nutrition, but VPS using hand portions was new for respondents to understand food portions according to needs.